Proapoptotic genes in cancer gene therapy - Missol-Kolka, Ewa; Mitrus, Iwona; Szala, Stanisław (Contemporary Oncology/Współczesna Onkologia, 2001)
The article describes prospects of using the so-called pro-apoptotic genes in gene therapy of neoplastic diseases. Apoptosis is a process that eliminates damaged cells unable to repair their incurred defects (for example mutations in their DNA, faulty proliferation patterns, etc.). In neoplastic diseases apoptosis becomes corrupted. Neoplastic cells become insensitive to the majority of signals that normally trigger apoptosis. In sum, their phenotype becomes apoptosis-resistant. One possible therapeutic strategy in cancer treatment is to destroy defective cells by endowing them with genes that encode the pro-apoptotic proteins. Their task is to restore apoptosis responsiveness of these cells. During gene therapy trials, both in vitro and in vivo, various pro-apoptotic genes have been tried (for example bax, bak, bim). Usually, growth inhibition has been obtained in primary tumors induced in experimental animals that have been administered such pro-apoptotic genes. However, this strategy has a serious drawback, namely its low specificity. These genes induce apoptosis in both normal and neoplastic cells, thus leading to damage of normal tissues also. Nonetheless, there are pro-apoptotic proteins that act specifically on abnormal cells and cause their death without affecting normal cells. Examples of such proteins involve viral Apoptin and E4orf4. Death induced by these proteins is caspase-independent. It neither depends on functional status of p53 gene nor on inhibitory effects of Bcl-2 family proteins. Although it shows morphological features of apoptosis, its time-course is considerably longer than that of typical apoptosis (it lasts up to several days). Therapeutic application of genes encoding these proteins is likely to circumvent problems associated with damage to normal tissues. In case of pro-apoptotic genes encoding endogenous eukaryotic proteins (for example Bax protein) specificity of expression may be assured by putting them under the control of promoters that are tumor-specific. Examples include hypoxia-induced promoter and telomerase gene promoter. Pro-apoptotic genes may be transferred into neoplastic cells in various manners, including electroporation and use of cationic liposomes or cationic polymers. However, viral carriers prove to be so far the most efficient type of vectors for such purposes, albeit they are nor devoid of inherent problems. In the case of pro-apoptotic genes, it is the production of adenoviral vectors that poses a problem as they contain a gene which is toxic to packaging cells. Possible solutions include use of binary systems comprising two adenoviral vectors. The first of them contains a pro-apoptotic gene remaining under the control of a promoter binding a specific, second vector-encoded protein, whose gene was placed under the control of a telomerase promoter. Expression of the pro-apoptotic gene takes place only upon co-transfection of target cells with both carriers. The strategy of using pro-apoptotic genes in the treatment of neoplastic diseases, apart from enabling selective and direct destruction of cancer cells via restoring their programmed death, may also ameliorate the therapeutic effect obtained if it is combined with radiotherapy and/or chemotherapy.